The Effect of Oil Shocks on Foreign Trade under Inflation and Exchange Rate Targeting Policies (In the Form of a Dynamic Stochastic General Equilibrium Model for Iran) - Behrad-Amin, Mehdi; Zamanian, Gholamreza; Esfandiari, Marzie (International Journal of Economics and Financial Issues, 2017)
In this study we examined the effect of oil shocks on Iran’s foreign trade in the presence of the exchange rate and inflation targeting policies. Therefore, we estimated an open economy new adjusted Keynesian DSGE model for Iran using Bayesian method under the assumption that these policies will have an important role in absorbing negative effects of oil shocks on the foreign trade. The results of model simulations show that the severity and duration of the negative effects of shock oil revenues have decreased on export and import in the case of inflation and exchange rate targeting, compared to the failure to adopt this policies. Also, the effects of the shock on the exports and imports of intermediate goods in the targeted exchange rate faster than the inflation targeting has gone out of the system, while the effects of the oil shock on imports of consumer goods in the case of inflation targeting is more quickly out of the system. In addition, in the event of a shock, changes in three variables is lower while targeted inflation. Keywords: Inflation targeting, Exchange rate targeting, Foreign trade, Oil shock, DSGE model JEL Classifications: C53, E52, E58,ØŒ F17ØŒ F14